Reactive functional polymer material and preparation method thereof
By introducing epoxy groups onto matrix I and coupling them with 4-OH-TEMPO, a stable reactive functional polymer material was prepared, which solved the problems of poor catalyst stability and low number of recycling times in the existing technology, and achieved efficient multiple recycling and simplified separation process.
Patent Information
- Application Number
- CN202411590780.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Existing reactive functional polymer catalysts have poor stability and performance during recycling, and require stringent experimental conditions, are costly, and are difficult to recycle efficiently multiple times.
By reacting matrix I with an epoxy reagent under alkaline conditions to generate matrix II with epoxy groups on its surface, and then coupling it with 4-OH-TEMPO through a spacer arm, a stable reactive functional polymer material is prepared.
The prepared polymer materials maintain high reaction efficiency during multiple cycles of use, simplifying the synthesis process, reducing costs, facilitating separation, and improving reaction efficiency and stability.
Smart Images

Figure CN119463286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a reactive functional polymer material and a preparation method thereof, belonging to the technical field of polymer materials. Background Art
[0002] Reactive functional polymer materials can be roughly divided into two types: 1) Polymer reaction reagents: small molecule reaction reagents are polymerized, or reactive groups are introduced into certain polymer skeletons to obtain polymer compounds with chemical reagent functions. Their chemical reactions are generally multiphase chemical reactions. 2) Polymer catalysts: small molecule catalysts are polymerized by polymerization, grafting, etc., so that the chemical structure with catalytic activity is combined with the polymer skeleton to obtain polymer materials with catalytic activity. Their catalytic reactions are generally multiphase catalytic reactions. Reactive functional polymer materials have broad application prospects in chemical synthesis, chemical reactions, drug delivery, bionic materials, smart materials and sensors.
[0003] Polymer catalysts have obvious advantages in applications. They have strong selectivity, catalyticity and stability, are easy to separate and recycle, and are environmentally friendly. However, there are also some drawbacks: for example, the experimental conditions are relatively demanding, requiring specific temperature, pressure and other conditions; the output is unstable, especially the existing polymer catalysts are rarely recycled and the effect is not good. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a reactive functional polymer material which has strong stability and can be recycled and reused multiple times.
[0005] Technical solution: The method for preparing the reactive functional polymer material provided by the present invention comprises the following steps:
[0006] (1) reacting substrate I with an epoxy reagent under alkaline conditions to obtain substrate II having epoxy groups on the surface, wherein the surface of substrate I contains active hydroxyl groups;
[0007] (2) 4-OH-TEMPO is coupled to the matrix II via a spacer arm to obtain a reactive functional polymer material.
[0008] Furthermore, the matrix I in step (1) comprises polystyrene / divinylbenzene, polymethacrylate or polyacrylamide.
[0009] Furthermore, the matrix I in step (1) is a porous microsphere with a pore size of The particle size is 5-100μm.
[0010] Furthermore, the epoxy reagent described in step (1) includes one or more of ethylene glycol glycidyl ether, neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,2-cyclohexanediol diglycidyl ether, glycidyl ether, pentaerythritol glycidyl ether or epichlorohydrin.
[0011] Furthermore, the preparation steps of step (1) include: dispersing the matrix I in an aqueous solution of NaOH or KOH, adding an epoxy reagent, stirring the reaction, filtering, and washing to neutrality to obtain a matrix II having epoxy groups on the surface.
[0012] Specifically, per 10g of substrate I, the substrate I is dispersed in 150-250mL of an aqueous solution containing 0.5-5.0mol / L of NaOH or KOH, 10-30mL of an epoxy reagent is added, and the reaction is stirred at 40-80°C for 3-6 hours, and then filtered and washed until neutral to obtain a substrate II having epoxy groups on the surface.
[0013] Furthermore, the preparation step of step (2) comprises: adding an alkaline solution to the matrix II, adding 4-OH-TEMPO after stirring, filtering after stirring for reaction, and washing to neutrality to obtain a reactive functional polymer material.
[0014] Furthermore, the preparation step of step (2) includes: adding an acidic solution to the matrix II, adding 4-OH-TEMPO after stirring, filtering after stirring for reaction, and washing to neutrality to obtain a reactive functional polymer material.
[0015] Furthermore, the preparation steps of step (2) include: dispersing the matrix II in an organic solvent, introducing nitrogen, deoxygenating, adding Lewis acid, stirring, adding 4-OH-TEMPO, continuing to stir the reaction, and then filtering and washing to neutrality to obtain a reactive functional polymer material.
[0016] Specifically, the matrix II is dispersed in 50-250 mL of an organic solvent, nitrogen is introduced, deoxygenation is performed for 30 minutes, 2-5 equivalents of Lewis acid are added, stirring is performed for 30 minutes under nitrogen, a small molecule reagent 4-OH-TEMPO is added, stirring is performed at 25-70° C., and then filtering and washing to neutrality to obtain a reactive functional polymer material.
[0017] The present invention also provides a reactive functional polymer material prepared according to the above preparation method.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following outstanding and significant advantages: the polymer material prepared by the present invention can be added in excess when participating in the reaction, so that the synthesis process is greatly simplified; the raw materials used to synthesize reactive functional polymer materials are cheap and easy to obtain, and the synthesis cost is low; the high specific surface area and good swelling properties of the prepared polymer material ensure the activity of the functional group and improve the reaction efficiency; the polymer material has strong stability, and the reaction efficiency decreases less after multiple cycles, which is economical and environmentally friendly; after the reaction is completed, only simple filtration is required to separate the polymer material from numerous impurities, and the separation process is simpler and more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the concentration standard curve of benzaldehyde.
[0020] Figure 2 This is the HPLC chart of benzaldehyde. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0022] Example 1
[0023] 1. In this embodiment, polymethacrylate base ball (Suzhou Saifen Technology Co., Ltd.; item number: 283960501) is used as matrix I, with a particle size of 60 μm and a pore size of The surface contains hydroxyl groups.
[0024] 2. Use a precision balance to accurately weigh 20 g of polymethacrylate base balls and add them to a 500 mL three-necked flask. Add 200 mL of 0.8 mol / L NaOH solution prepared in advance to the flask, stir mechanically at 150 rpm for 30 minutes, add 20 mL of ethylene glycol glycidyl ether, stir at 50 ° C for 3 hours, filter with a Buchner funnel after the reaction is completed, wash with 200 mL of ethanol, and then wash with ultrapure water for an indefinite amount until neutral, drain and set aside to obtain a matrix II with epoxy groups on the surface.
[0025] 3. Transfer the above matrix II to a 500mL three-necked flask, add 200mL 2mol / L NaOH aqueous solution, stir mechanically at 150rpm for 10 minutes, add 8g 4-OH-TEMPO, stir at 50℃ for 6 hours, filter with a Buchner funnel after the reaction, wash with 200mL ethanol, and then wash with ultrapure water for an indefinite amount until neutral, and drain to obtain a new type of reactive functional polymer material. Each spacer arm of the new type of reactive functional polymer material contains only one TEMPO.
[0026] The reaction equation is as follows:
[0027]
[0028] Example 2
[0029] Steps 1 and 2 are the same as in Example 1, and step 3 is:
[0030] The above matrix II was transferred to a 500mL three-necked flask, 200mL of 2mol / L H2SO4 aqueous solution was added, mechanically stirred at 150rpm for 10 minutes, 8g of 4-OH-TEMPO was added, and stirred at 50℃ for 5 hours. After the reaction, it was filtered with a Buchner funnel, washed with 200mL of ethanol, and then washed with ultrapure water for an indefinite amount until neutral, and dried to obtain a new type of reactive functional polymer material. Each spacer arm of the new type of reactive functional polymer material contains only one TEMPO.
[0031] Example 3
[0032] Steps 1 and 2 are the same as in Example 1, and step 3 is:
[0033] The above matrix II was transferred to a 500mL three-necked flask, 200mL of 1,4-dioxane was added, mechanically stirred at 150rpm for 10 minutes, nitrogen was introduced, deoxygenated for 30 minutes, 2-5 equivalents of AlCl3 Lewis acid were added, stirred under nitrogen for 30 minutes, 8g of 4-OH-TEMPO was added, and stirred at 50°C for 8 hours. After the reaction was completed, it was filtered with a Buchner funnel, washed with 200mL of ethanol, and then washed with ultrapure water for an indefinite amount until neutral, and dried to obtain a new type of reactive functional polymer material.
[0034] Example 4
[0035] The steps are basically the same as those in Example 3, except that the epoxy reagent in step 2 is replaced by 20 mL of neopentyl glycol diglycidyl ether.
[0036] Example 5
[0037] The steps are basically the same as those in Example 3, except that the epoxy reagent in step 2 is replaced by 20 mL of 1,4-butanediol diglycidyl ether.
[0038] Example 6
[0039] The steps are basically the same as those in Example 3, except that the epoxy reagent in step 2 is replaced by 20 mL of glycidyl ether. The novel reactive functional polymer material contains two TEMPOs on each spacer arm.
[0040] The reaction equation is as follows:
[0041]
[0042] Example 7
[0043] The steps are basically the same as those in Example 3, except that the epoxy reagent in step 2 is replaced by 20 mL of pentaerythritol glycidyl ether. Each spacer arm of the novel reactive functional polymer material contains four TEMPOs.
[0044] Example 8
[0045] The steps are basically the same as those in Example 3, except that the base ball in step 1 is replaced with a PSDVB base ball (Suzhou Saifen Technology Co., Ltd.; item number: 220015501) as the matrix I, with a particle size of 15 μm and a pore size of The surface contains hydroxyl groups.
[0046] Comparison Example
[0047] The commercially available Merrifield resin (Merrifield resin purchased from NANKAI HECHENG with a loading of 1 mmol / g) was used directly without treatment. The solvent was analytically pure or chemically pure and was treated with anhydrous solvent before use. Other reagents were not further purified. Transferred to a 500 mL three-necked flask, 200 mL of 0.8 mol / L NaOH solution prepared in advance was added to the above flask, mechanically stirred at 150 rpm for 30 minutes, 8 g of 4-OH-TEMPO was added, and stirred at 50 ° C for 24 hours. After the reaction was completed, it was filtered with a Buchner funnel, washed with 200 mL of ethanol, and then washed with ultrapure water for an indefinite amount until neutral, and then dried for standby use to obtain a resin-loaded catalyst.
[0048] Reaction Test 1
[0049] Reaction conditions: In a 500mL three-necked flask, add 10g of benzyl alcohol and 20mL of dichloromethane solution, stir mechanically at 150rpm for 10 minutes to disperse evenly, then add 5mol% of the catalyst prepared in the above example, 10mol% of NaBr and 1.1eqNaOCI, and stir at room temperature for 5h.
[0050] The yield of the target compound was detected by HPLC standard curve method as follows:
[0051] Chromatographic conditions:
[0052] Instrument: Agilent 1260 InfinityⅡ;
[0053] Wavelength: 280nm;
[0054] Flow rate: 0.35ml / min;
[0055] Collection time: 18min;
[0056] Injection: 5 μL;
[0057] Mobile phase: 150 mM PB, pH 7.0;
[0058] Chromatographic column: Zenix SEC-300, 4.6mm*300mm
[0059] Standard curve preparation
[0060] The following test data are all test results under the equipment (YZ-LC-01). The retention time of the following samples is based on benzaldehyde as the quality control sample as the standard.
[0061] Starting with benzaldehyde solution, dilute it in half with acetonitrile, and the resulting concentration will also be reduced in half. For the specific working solution preparation, refer to Table 1 (taking 77 mg / mL as an example):
[0062] Table 1
[0063]
[0064]
[0065] According to the table above, with the addition of the 77mmol / mL mother solution and the 0mmol / mL blank (which can be replaced by 1mL acetonitrile) concentration point, a total of 8 concentration points can be obtained. These 8 concentration points are placed in the HPLC sample tray in ascending order for testing.
[0066] Note: The above concentrations are reference values. The concentrations can be reduced proportionally, but must cover the test range.
[0067] Table 2
[0068]
[0069] The results show that the polymer material prepared by the preparation method of Example 3 has the best effect. Because the small molecules we selected contain highly active free radicals, they may be partially inactivated under acidic and alkaline conditions, thereby affecting their catalytic efficiency. Therefore, the method of Example 3 is selected as the best preparation method.
[0070] The results show that there is little difference between Example 8 and Example 3, and both have good effects, because the two base balls selected are both high-strength hard base balls, which are relatively good in both rigidity and acid and alkali resistance, and therefore have little effect on the results.
[0071] Reaction Test 2
[0072] The reaction liquids obtained by using the catalysts of Examples 1-3 and the reference example were filtered, and the filter cakes were washed with 100 mL of 1,4-dioxane and pure water respectively until the filtrate was neutral, and then rinsed with dichloromethane solution three times. The above catalysts were then used to continue the reaction under the conditions of reaction test 1, and a total of five reactions were performed.
[0073] Table 3
[0074] Case Example 1 Example 2 Example 3 Comparison Example Reaction yield after one cycle (%) 71 79 89 51 Reaction yield after secondary cycle (%) 70 79 87 45 Reaction yield after three cycles (%) 70 77 86 41 Reaction yield after four cycles (%) 65 75 85 36 Reaction yield after five cycles (%) 64 72 83 30
[0075] The results show that the catalyst of the present application has strong stability and good recycling effect. The yield of the first reaction is only 6-7% lower than that of the fifth reaction. Among them, the catalyst prepared in Example 3 has the best effect.
[0076] Reaction Test 3
[0077] The catalysts in Examples 3 to 5 and the control example were tested in this reaction, and the testing method was the same as that in Reaction Test 2.
[0078] Table 4
[0079] Case Example 4 Example 5 Example 3 Comparison Example Reaction yield after one cycle (%) 93 78 89 51 Reaction yield after secondary cycle (%) 91 78 87 45 Reaction yield after three cycles (%) 89 76 86 41 Reaction yield after four cycles (%) 88 74 85 36 Reaction yield after five cycles (%) 87 72 83 30 Reaction yield after five cycles (%) 89 63 83 30
[0080] In order to improve the catalytic efficiency, the present invention verifies the effect of controlling the length of the spacer arm on the base ball to improve the catalytic efficiency. The proper increase of the spacer arm is conducive to improving the catalytic efficiency, but the longer the spacer arm is, the better. The present invention confirms that the length of the spacer arm bonded with neopentyl glycol diglycidyl ether is just right, and then as the length increases, the catalytic efficiency is lower, and the recycling reaction efficiency is greatly reduced. It may be that the partition wall is too long, and under strong reaction conditions, some of it will fall off.
[0081] Reaction Test 4
[0082] The catalysts in Examples 3, 6, 7 and the control example were tested in this reaction, and the testing method was the same as that in Reaction Test 2.
[0083] Table 5 Case Example 6 Example 7 Example 3 Comparison Example Reaction yield after one cycle (%) 95 68 89 51 Reaction yield after secondary cycle (%) 93 66 87 45 Reaction yield after three cycles (%) 91 66 86 41 Reaction yield after four cycles (%) 91 64 85 36 Reaction yield after five cycles (%) 89 63 83 30
[0084] In order to improve the catalytic efficiency, the present invention bonds multiple 4-OH-TEMPO on the base ball through the spacer arm. Experiments show that the catalytic efficiency can indeed be improved, but the number of bonded catalysts is not necessarily the more the better. The present invention confirms that the best bonding is when there are two 4-OH-TEMPO. As the number increases, the catalytic efficiency is lower. It may be that there are too many small molecules bonded, and they will produce a spatial shielding effect on each other on the surface of the ball, which is not conducive to its catalytic reaction.
Claims
1. A method for preparing a reactive functional polymer material, characterized in that: The following steps are involved: (1) reacting substrate I with an epoxy reagent under alkaline conditions to obtain substrate II having epoxy groups on the surface, wherein the surface of substrate I contains active hydroxyl groups; (2) 4-OH-TEMPO is coupled to the matrix II via a spacer arm to obtain a reactive functional polymer material.
2. The preparation method according to claim 1, characterized in that: The matrix I described in step (1) comprises polystyrene / divinylbenzene, polymethacrylate or polyacrylamide.
3. The preparation method according to claim 1, characterized in that: The matrix I described in step (1) is a porous microsphere with a pore size of The particle size is 5-100μm.
4. The preparation method according to claim 1, characterized in that: The epoxy reagent described in step (1) includes one or more of ethylene glycol glycidyl ether, neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,2-cyclohexanediol diglycidyl ether, glycidyl ether, pentaerythritol glycidyl ether or epichlorohydrin.
5. The preparation method according to claim 1, characterized in that: The preparation steps of step (1) include: dispersing the matrix I in an aqueous solution of NaOH or KOH, adding an epoxy reagent, stirring for reaction, filtering, and washing to neutrality to obtain a matrix II having epoxy groups on the surface.
6. The preparation method according to claim 1, characterized in that: The preparation steps of step (2) include: adding alkaline solution to the matrix II, adding 4-OH-TEMPO after stirring, filtering after stirring and washing to neutrality to obtain a reactive functional polymer material.
7. The preparation method according to claim 1, characterized in that: The preparation steps of step (2) include: adding an acidic solution to the matrix II, adding 4-OH-TEMPO after stirring, filtering after stirring for reaction, and washing to neutrality to obtain a reactive functional polymer material.
8. The preparation method according to claim 1, characterized in that: The preparation steps of step (2) include: dispersing the matrix II in an organic solvent, introducing nitrogen, deoxygenating, adding Lewis acid, stirring, adding 4-OH-TEMPO, continuing to stir the reaction, and then filtering and washing to neutrality to obtain a reactive functional polymer material.
9. A reactive functional polymer material prepared according to the preparation method according to any one of claims 1 to 8.